2010
DOI: 10.1371/journal.pone.0013968
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Strategy for Characterizing Bacterial Proteomes across Species in the Absence of Genomic Sequences

Abstract: Global protein identification through current proteomics methods typically depends on the availability of sequenced genomes. In spite of increasingly high throughput sequencing technologies, this information is not available for every microorganism and rarely available for entire microbial communities. Nevertheless, the protein-level homology that exists between related bacteria makes it possible to extract biological information from the proteome of an organism or microbial community by using the genomic sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…As the genome of Shewanella sp. HRCR‐1 has not been sequenced, peptides were identified by searching against in silico tryptic sequences derived from in‐house S. oneidensis MR‐1, MR‐4 and MR‐7 protein FASTA protein sequences (Turse et al ., 2010). The results showed that a total of 425 ( S. oneidensis MR‐1), 323 ( S. oneidensis MR‐4) and 316 ( S. oneidensis MR‐7) proteins were identified with high confidence (at least two unique peptides) in the EPS samples (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…As the genome of Shewanella sp. HRCR‐1 has not been sequenced, peptides were identified by searching against in silico tryptic sequences derived from in‐house S. oneidensis MR‐1, MR‐4 and MR‐7 protein FASTA protein sequences (Turse et al ., 2010). The results showed that a total of 425 ( S. oneidensis MR‐1), 323 ( S. oneidensis MR‐4) and 316 ( S. oneidensis MR‐7) proteins were identified with high confidence (at least two unique peptides) in the EPS samples (Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…One bacterial isolate has been assigned to genus Ruegeria after a rapid MALDI MS screening of 30 seawater bacterial isolates, demonstrating the usefulness of this combined proteogenomic approach for environmental monitoring of complex environments. A trans‐organism composite proteomics strategy has been applied to characterize unsequenced environmental bacterial isolates similar to Shewanella , as inferred from 16S ribosome comparison . Up to 500 Shewanella proteins, mapped to core pathway processes, have been identified in each unsequenced strain.…”
Section: Discussionmentioning
confidence: 99%
“…While the field is too vast to adequately detail in this limited review, it is worth noting that some of the basic database searching and data extraction methodologies have become quite standardized and fairly routine, leaving more attention to be paid to data mining and analyses. This has led to a noticeable increase in the number of interdisciplinary interactions between experimental and computational researchers, often focused on design of an integrated approach for specific problems, such as characterizing proteomes across microbial species in the absence of specific genomic data [28], or evaluating new approaches to integrate metagenomic and metaproteomics information [29,30].…”
Section: Bioinformatic Considerationsmentioning
confidence: 99%